1995
DOI: 10.1172/jci118120
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced G protein activation in immortalized lymphoblasts from patients with essential hypertension.

Abstract: (GTPyS), to membrane G proteins were not different in NT and HT cell lines. However, PAF-and mastoparan-stimulated binding of GTPyS to G proteins, which was fully PTX-sensitive, was 2.5-fold higher in HT than NT cell lines. These data suggest an enhanced receptor-mediated activation of PTX-sensitive G proteins despite unchanged receptor and G protein expression. Thus, this study not only suggests that enhanced signal transduction and cell proliferation are abnormalities in a certain group of patients with esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
134
0
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 36 publications
1
134
0
5
Order By: Relevance
“…One possible mechanism for the higher systolic blood pressure might be chronic sodium retention and expansion of the circulating volume as a consequence of the higher activity of the Na + /H + exchanger. 2,4 Several observations support this hypothesis. In one population-based study, plasma renin activity was decreased in the presence of the T allele.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…One possible mechanism for the higher systolic blood pressure might be chronic sodium retention and expansion of the circulating volume as a consequence of the higher activity of the Na + /H + exchanger. 2,4 Several observations support this hypothesis. In one population-based study, plasma renin activity was decreased in the presence of the T allele.…”
Section: Discussionmentioning
confidence: 88%
“…This mutation leads to a gain in function 2 and entails stimulation of the ubiquitously expressed Na + /H + exchanger. 3,4 de la Sierra et al 5 observed that in patients with essential hypertension, left ventricular hypertrophy was associated with increased Na + /H + exchanger activity.…”
Section: Introductionmentioning
confidence: 99%
“…The use of LCLs has been previously proven to be instrumental in uncovering important pathogenic mechanisms in other diseases, such as hypertension, glycogen and lipid storage diseases, chronic granulomatous disease, hematologic disorders, and solid tumors (27)(28)(29)(30)(31)(32)(33). One illustrative example is essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A common single nucleotide polymorphism (SNP), rs5443 (C825T), located on exon 10 of the GNB3 gene has received much attention. The T allele of the GNB3 rs5443 SNP has been shown to cause enhanced G-protein activation and thus increased in vitro cell proliferation (Siffert et al 1995). The T allele of the GNB3 rs5443 SNP was identified to be associated with obesity, hypertension, and atherosclerosis (Benjafield et al 2001;Hegele et al 1999;Klenke et al 2011;Poch et al 2002;Siffert 2005;Siffert et al 1999).…”
Section: Introductionmentioning
confidence: 99%